A simple semi-dynamic model of the subduction zone: Effects of a moving plate boundary on the small-scale convection under the island arc - Honda, Satoru (Geophysical journal international, 2008)
A simple semi-dynamic numerical model of the subduction zone, which incorporates the plate velocity and a moving plate boundary as a priori constraints, has been developed. This model may be useful for studying specific subduction zones where a history of kinematic movements of plates is well constrained. As an application of this model, the effects of a moving plate boundary on the nature of the small-scale convection in the mantle wedge were studied. Under the restriction of given ‘relative’ velocity between two converging plates, the ‘absolute’ velocity of each plate was changed and I found that the characteristics of small-scale convection are not significantly affected by the movement of the plate boundary, at least within the parameter range used in this study. I also found a small systematic change, which may be related to the difference of the heat supply to the mantle wedge, caused by the moving plate boundary. Thus, the model with a fixed ‘continental’ plate and moving ‘oceanic’ plate with a given relative velocity may be sufficient for studying the present subject. This model can be extended into a simple 3D subduction zone model.